2014
DOI: 10.1097/bot.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiographic Stress Tests for Syndesmotic Instability of Supination–External Rotation Ankle Fractures

Abstract: Lateral stress test with widening of the tibiofibular clear space is the preferred indicator of syndesmotic instability. The external rotation stress is a poor indicator of syndesmotic injury in the setting of deltoid ligament injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…Measurements at each stage of ligament transection were then repeated under a 100-N lateral hook test, which has been shown to be superior to external rotation stress test when diagnosing syndesmotic instability. 11,23 The amount of force was selected based on the study of Stoffel et al, 23 which demonstrated that >100 N did not substantially increase the tibiofibular diastasis. The lateral hook test was performed by pulling the fibula laterally 5 cm above the ankle mortise via a force gauge ( Figure 1B).…”
Section: Arthroscopic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements at each stage of ligament transection were then repeated under a 100-N lateral hook test, which has been shown to be superior to external rotation stress test when diagnosing syndesmotic instability. 11,23 The amount of force was selected based on the study of Stoffel et al, 23 which demonstrated that >100 N did not substantially increase the tibiofibular diastasis. The lateral hook test was performed by pulling the fibula laterally 5 cm above the ankle mortise via a force gauge ( Figure 1B).…”
Section: Arthroscopic Measurementsmentioning
confidence: 99%
“…Prior studies that investigated the deltoid's contribution toward syndesmotic stability relied on plain radiographs and intraoperative fluoroscopy, which may be limited in their ability to identify less pronounced syndesmotic instability. 4,11 Advances in ankle arthroscopy allow direct inspection of the syndesmosis, 5,15,24,25 affording the opportunity to directly visualize even subtle syndesmotic instability. 9,16,27 Variable anatomic locations within the distal tibiofibular joint have historically been used to diagnose syndesmotic instability, including the center, anterior, and posterior aspect of the incisura.…”
Section: Introductionmentioning
confidence: 99%
“…A cadaveric study recently evaluated these 2 stress tests, but cadaveric studies do not account for the complexity of damage to the soft tissue structures in a traumatic event. 15,18,19 Indeed, MRI studies after ankle fractures show that many of these fractures will have partial tears in the primary ankle stabilizers. 20,21 Our study tested the hypothesis that stress external rotation radiographs after fixation of the unstable ankle fracture demonstrate mortise instability greater than a direct lateral fibular stress.…”
Section: Discussionmentioning
confidence: 98%
“…The bone block was supplemented with a tetracortical syndesmotic screw. Follow-up demonstrated improved average AOFAS scores (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92) in 12 patients treated greater than 2 years after initial injury with an average follow-up of 25 months.…”
Section: Surgical Treatment Reconstructionmentioning
confidence: 95%